O interpretacijah verjetnosti - Trpin, Borut (Analiza: časopis za kritično misel, 2025)
On the Interpretations of ProbabilityWe often talk about probability in a completely everyday context and understand it intuitively. The problem arises when we try to define more precisely what probability is. The heterogeneity is reflected in the large number of different theoretical interpretations of probability. For a better understanding of the plurality of approaches, the first part of the paper provides a brief historical overview of the development of interpretations of probability and probability calculus. In the second part, various key interpretations are presented and critically evaluated: classical, logical, subjective, frequentist, and the propensity interpretation. The paper concludes with a brief analysis of how interpretations of probability are embedded in a broader philosophical context and highlights one of the open issues in this field: imprecise probabilities.
Keywords: probability; interpretations of probability; epistemology; philosophy of science; philosophy of statistics